Patency of permanent vascular access creation in paediatric patients with end stage renal disease - Ho, Hui Lian; Ahmad Sukari Halim; Arman Zaharil Mat Saad; Wan Azman Wan Sulaiman; Mohamad Ikram Ilias (Malaysian Medical Association, 2021)
Renal transplant is the first-line therapy in paediatric patients with end-stage renal disease (ESRD). Wong HS and Goh BL reported up to 79% of 1061 paediatric patients still require long-term haemodialysis (HD).1 The lack of deceased and living donors is attributable to the poor awareness, cultural and religious grounds. Permanent vascular access (PVA) in paediatrics therefore, serves more as a long term treatment rather than a bridging therapy. We observed 5 children and an adolescent, all with previous indwelling catheters, who underwent arteriovenous fistula (AVF) creation and report the outcomes. The aim of this report is to determine the factors that influence the longterm patency of paediatric AVF. Factors such as body weight, vessel diameter, preoperative preparations, microsurgical technique and postoperative maintenance are discussed. In addition, considerations on the choice and timing of PVA is highlighted.